Pseudohexagonal Nb2O5‐Decorated Carbon Nanotubes as a High‐Performance Composite Anode for Sodium Ion Batteries. Issue 23 (11th October 2022) - Chen, Guanxu; Chen, Jintao; Parkin, Ivan P.; He, Guanjie; Miller, Thomas S.
Abstract: To promote the commercial application of sodium ion batteries (SIBs), new high‐stability and high‐capacity anode materials are needed. Metal oxides show great promise, but significant issues relating to their low electrical conductivity and unstable structure during charge storage must be resolved. Herein, a new composite anode consisting of pseudohexagonal Nb2 O5 (TT‐Nb2 O5 ) nanoparticles strongly anchored to carbon nanotubes (CNT) through a glucose‐derived carbon framework (Nb2 O5 /g‐CNT) was synthesised and assessed for use as the anode in SIBs. This represents the first application of TT‐Nb2 O5 in SIBs. The composite is shown to offer high specific capacity (203 mAh g −1 at 0.2 A g −1 ), good rate capability (53 mAh g −1 at high current density of 5 A g −1 ), and a high‐capacity retention rate (135 mAh g −1 at 0.2 A g −1 between 25 and 300 cycles). This is attributed to high electrical conductivity and flexibility offered by the designed carbon framework, the superior capacity of the TT‐Nb2 O5 and the linkage between the two provided by the bonding glucose derived carbon. This work therefore demonstrates a scalable route for the application of metal oxides in future high‐performance SIB systems. Abstract : Pseudohexagonal Nb2 O5 (TT‐Nb2 O5 ) has been applied in sodium ion batteries (SIBs) for the first time. Lower synthesis temperatures, improved conductivity and stability were achieved by the introduction of a designed carbon framework. The TT‐Nb2 O5 /carbon nanotube composite exhibits high specific capacity (135 mAh g −1 at 0.2 A g −1 ) in long cycles and good rate capability (53 mAh g −1 at high current density of 5 A g −1 ). The outstanding electrochemical performance is attributed to the superior electrical conductivity and connectivity, optimal mass transport conditions and the mechanical strength and durability established by the strongly linked TT‐Nb2 O5 and MWCNT network. This study provides a cost‐effective route to the application of Nb2 O5 in SIBs.